The state of the art of the Brazilian Bill on Artificial Intelligence with a focus on civil responsibility - Vincenzo Calderonio (Rivista Italiana di Informatica e Diritto)
Brazil is developing a regulatory framework for artificial intelligence (AI), which began in 2019 with a public consultation and culminated in Bill PL No. 2338/2023, under discussion in Parliament. This note outlines the state of the art, focusing particularly on the issue of civil responsibility.